Thalidomide stimulates vessel maturation and reduces epistaxis in individuals with hereditary hemorrhagic telangiectasia - Lebrin, Franck; Srun, Samly; Raymond, Karine; Martin, Sabrina; van den Brink, Stieneke; Freitas, Catarina; Bréant, Christiane; Mathivet, Thomas; Larrivée, Bruno; Thomas, Jean-Léon; Arthur, Helen M; Westermann, Cornelis J J; et al. (Nature medicine, 2010)
Individuals with the disease hereditary hemorrhagic telangiectasia have vascular defects that lead to frequent hemorrhages. Franck Lebrin et al . now show that thalidomide, tested as a therapy in a small set of individuals with this disease, lowers the frequency of hemorrhaging and the need for blood transfusions. The authors tie the antihemorrhagic effects of thalidomide to its ability to promote blood vessel maturation through effects on PDGF-B expression by endothelial cells and on pericyte cell proliferation ( pages 370–372 ). Hereditary hemorrhagic telangiectasia (HHT) is an inherited disorder characterized by vascular malformations. Many affected individuals develop recurrent nosebleeds, which can severely affect their quality of life and are clinically difficult to treat. We report here that treatment with thalidomide reduced the severity and frequency of nosebleeds (epistaxis) in the majority of a small group of subjects with HHT tested. The blood hemoglobin levels of the treated individuals rose as a result of reduced hemorrhage and enhanced blood vessel stabilization. In mice heterozygous for a null mutation in the Eng gene (encoding endoglin), an experimental model of HHT, thalidomide treatment stimulated mural cell coverage and thus rescued vessel wall defects. Thalidomide treatment increased platelet-derived growth factor-B (PDGF-B) expression in endothelial cells and stimulated mural cell activation. The effects of thalidomide treatment were partially reversed by pharmacological or genetic interference with PDGF signaling from endothelial cells to pericytes. Biopsies of nasal epithelium from individuals with HHT treated or not with thalidomide showed that similar mechanisms may explain the effects of thalidomide treatment in humans. Our findings demonstrate the ability of thalidomide to induce vessel maturation, which may be useful as a therapeutic strategy for the treatment of vascular malformations.